Effects of Stores’ Environmental Components on Chinese Consumers’ Emotions and Intentions to Purchase Luxury Brands: Integrating Partial Least Squares-Structural Equation Modeling and Fuzzy-Set Qualitative Comparative Analysis Approaches - Yang, Shaohua; Isa, Salmi Mohd; Wu, Hongyan; Thurasamy, Ramayah; Fang, Xi; Fan, Yedan; Liu, Danping (Frontiers in Psychology, 2022)
Abstract Purpose – This paper investigates the effects of stores’ environmental components (i.e., lighting, cleanliness, scent, design, layout, music, and employee interaction) on Chinese consumers’ emotions and intentions to purchase luxury brands. Design/methodology/approach – Data were collected from Chinese consumers who have purchased luxury brands from retail stores. Partial least squares-structural equation modeling (PLS-SEM) and fuzzy-set qualitative comparative analysis (fsQCA) were employed for data analysis. Findings – The results of PLS-SEM indicated that three dimensions of the store environment (i.e., music, scent, and employee interaction) directly and significantly influenced Chinese consumers’ emotions. However, fsQCA revealed greater heterogeneity among respondents by highlighting stores’ environmental components and Chinese consumers’ emotions. Originality/value – This study enriches the empirical evidence on stores’ environmental components by constructing a composite picture of these dimensions within a luxury brand context. The present study may be one of the first to examine the effects of stores’ environmental components on Chinese consumers’ emotions and purchase intentions, applying both symmetrical test (PLS-SEM) and asymmetrical test (fsQCA) approaches to determine significant components of the store environment as well as component combinations that predict Chinese consumers’ emotions and purchase intentions.